Human Resource Management Practices in Small and Medium Enterprises - Ray, Ram Pujan (Patan Prospective Journal, 2022)
This article analyzes diverse aspects of human resource management as practiced in small and medium scale businesses. The significance of human resource management has increased with the expansion of businesses at different levels due to the liberalization of market and trades across the world. The role of human resources in corporate organizations is crucial in the sense that the strength of people determines the growth of businesses. Human resources are taken as the most precious asset of SME. To reach its values the business must pay a huge importance in human resource management. The implementation of enterprise strategy relies on the employee’s quality as reflected in the entire process of engagement in the world of business. This paper has aimed to demonstrate the implementation of human resource practice and their impact in Small and Medium Enterprise (SME) performance. The data used in the paper have been from secondary sources including articles, reports and dissertations. The existing literature demonstrates the management of human resources is aspiring in the business world. Both management and implementation of human resources has influenced the success of small and medium enterprises. Indeed, the commendable management of human resource helps three fundamental intents of each enterprise: surviving, increasing and raising their incomes. The paper investigates into the role of Small Scale Enterprises (SMEs) in the manufacturing sector that contributes to the growth of economy. Indeed, small-scale enterprises are important for modern economy as it widely contributes to employment growth as well. The development of a country depends on economic prosperity. Managing human resources in businesses can help to enhance the status of corporate world that aims to multiply economy of all aspects of society. As business establishments are human organizations, people are very indispensable in its existence and success. The study has explored that human resource development is significant to any organizations ranging from small to large scale enterprise because it is well known that no business can exist without human beings. It is recommended that SMEs business should clearly define recruitment policies in consistency with the existing laws of a particular nation. Besides, there should be consistency in training activities, the owners of SMEs business should ensure that training offered to employees at all levels is pertinent to their needs. Overall, human resource management practices play a significant role in affecting labor productivity in manufacturing companies.